FIRST DIAMONDS FROM PLACERS IN PRIMORIE - Shcheka S.A.; Ignat'ev A.V.; Nechaev V.P.; Zvereva V.P. (My University, 2006)
The paper reports the results obtained by the detailed studying of carbonado (the first find in a gold placer in Primorie) and a collection of diamonds that was confiscated in 1937 from a poaching small digger and was kept safe at the Nezametnyi mine (near the village of Vostretsovo), which had developed this placer deposit. In the concentrate from the placer, carbonado is associated with green corundum, various ilmenite, zircon titanian amphiboles and pyroxenes, rutile, anatase, and fragments of subvolcanic biotite picrites. All of these minerals, native aluminum, and tin occur as inclusions in the diamonds. The carbonado from Primorie was determined to be practically identical to this mineral from Brazil, has a porous structure, is characterized by orange luminescence, contains inclusions of Y, Ce, La, Ba, and Sr phosphates, and has an isotopically light composition of its carbon (13C from −25 to −32‰). Pores of the carbonado aggregates contain clusters of diamond crystals. The collection of diamonds from an unknown source included six gem-quality transparent crystals, one rounded ballas, two cuboctahedral crystals (one of greenish and the other of silver-gray color, both with outer coats), and one black carbonado grain.